EVALUATION THE USE OF IRAQI PORCELANITEROCKS AS LOOSE ABRASIVE POWDERS - حبيب حبيب (Iraqi Journal of Science, 2024)
Applied study was carried out on the Iraqi porcelanite rocks to determine theircapability and uses as a loose abrasive powder to abrade copper and aluminium,being soft metals and commonly used in different industrial purpose. Three differentsamples of porcelanite were selected from three different places in the Iraqi westerndesert, and which were as follows: Safra member sample (Late Cretaceous),Traifawi member sample (Early Paleocene)- Akashat location and Traifawi membersample (Early Paleocene)- H3 location. Chemical, mineralogical analyses andmicroscopic studies were carried out on those samples. The three samples wereground at different time intervals. Discoidal samples of copper and aluminiummetals were polished by using specimens of powdered porcelanite samples ofdifferent grains size ranging between (75-250) μm and (36-63) μm. The metalsamples then buffed using two grains size as (20-36)μm and < 20 μm respectively.Evalution tests including surface roughness test (Ra) and Reflectivity test (R%) werecarried out on copper and aluminium samples. The results showed that Iraqiporcelanite samples were good enough for abrading those two metals.